MANAJEMEN KELOMPOK KERJA GURU (KKG) DALAM UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU DI SD NEGERI KERTARAHAYU KECAMATAN CILAKU KABUPATEN CIANJUR - Dessy Ismaya Firmani; Idis Suherlan; Miranty Nurhayati; Yulia Rusmiati; Deni Hendrawan; Uyun Supyan Sauri (STKIP Subang, 2026)
This study aims to describe the management of the Teachers’ Working Group (KKG) in improving teachers’ professional competence at SD Negeri Kertarahayu, Cilaku District, Cianjur Regency. The research employed a qualitative descriptive approach, with data collected through observations, interviews, and document analysis involving the principal, KKG administrators, and participating teachers. The findings reveal that KKG management has been implemented through needs-based program planning, the organization of discussions, training sessions, lesson plan development, and the sharing of best teaching practices. Regular evaluations are conducted to measure program effectiveness and its impact on teachers’ professional development. Supporting factors include strong principal support, active teacher participation, and effective collaboration among KKG members. Meanwhile, limited time, inadequate facilities, and teachers’ administrative workloads serve as major challenges. Overall, KKG management has contributed positively to enhancing teachers’ professional competence, particularly in subject-matter mastery, instructional material development, and the application of innovative teaching strategies.